Experimental and Numerical Realization of Chaotic Intermittency Phenomena in a Fourth-order Autonomous Electric Circuit - V. Balachandran3*, S. Manimaran1, G. Kandiban2 and (Recent Research in Science and Technology, 2010)
Abstract In this work a fourth-order autonomous electric circuit. This circuit, which is capable of realizing the behavior of every member of the Chuaâ€™s family, consists of just five linear elements (resistor, inductors, and capacitors) and a smooth cubic nonlinear resistor. The route followed is a transition from regular behavior to chaos and then to intermittency phenomena through boundary condition, as the system parameter is varied. The chaotic intermittency phenomena, characterized by two positive Lyapunov exponents are described by set of four coupled first-order ordinary differential equations. This has been investigated extensively using laboratory experiments and numerical analysis. Keywords: Fourth-order autonomous electric circuit; Smooth cubic nonlinearity; Chaotic intermittency; Lyapunov exponents <span style="font-size: 10pt; line-height: 200%; font-family: ";Arial Narrow";,";sans-serif";; letter-spacing: -0.3pt; mso-fareast-font-family: SimSun; mso-fareast-language: EN-SG; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-SG; mso-bidi-language: AR-SA;" lang="EN-SG">